2022
DOI: 10.1093/genetics/iyac003
|View full text |Cite
|
Sign up to set email alerts
|

WormBase in 2022—data, processes, and tools for analyzing Caenorhabditis elegans

Abstract: WormBase (www.wormbase.org) is the central repository for the genetics and genomics of the nematode Caenorhabditis elegans. We provide the research community with data and tools to facilitate the use of C. elegans and related nematodes as model organisms for studying human health, development, and many aspects of fundamental biology. Throughout our 22-year history, we have continued to evolve to reflect progress and innovation in the science and technologies involved in the study of C. elegans. We strive to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
162
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(190 citation statements)
references
References 50 publications
3
162
0
Order By: Relevance
“…0 of 72 progeny from it!s37 + I + puf-ll(tn1824) parents carried a recombinant it!s37 puf-ll(tn1824) chromosome, while 5 of 64 progeny from it!s37 + I + puf-3(tn1820) parents carried a recombinant it!s37 puf-3(tn1820) chromosome. Together, these observations suggested that it!s37 is ∼7.8 map units to the left of puf-3 , in good agreement with the relative genetic positions of puf-ll and puf-3 described in WormBase (http://www.wormbase.org, release WS278; Davis et al . 2022).…”
Section: Methodssupporting
confidence: 81%
“…0 of 72 progeny from it!s37 + I + puf-ll(tn1824) parents carried a recombinant it!s37 puf-ll(tn1824) chromosome, while 5 of 64 progeny from it!s37 + I + puf-3(tn1820) parents carried a recombinant it!s37 puf-3(tn1820) chromosome. Together, these observations suggested that it!s37 is ∼7.8 map units to the left of puf-3 , in good agreement with the relative genetic positions of puf-ll and puf-3 described in WormBase (http://www.wormbase.org, release WS278; Davis et al . 2022).…”
Section: Methodssupporting
confidence: 81%
“…Whilst the absence of nape in some species may be explained by genome quality, in other species with robust genome data an alternative AEA synthesis pathway may exist (see below). Previous studies have demonstrated the presence of two, functionally divergent, nape orthologs in C. elegans that occupy adjacent genomic positions ( nape -1, IV:3739520..3740880 ; nape -2, IV:3735470..3738925; [WormBase; (Davis et al, 2022)], share 73% sequence identity, and display complete conservation of the NAPE-PLD signature sequence (Harrison et al, 2014). Our pan-phylum analysis confirms that C. elegans is the only nematode species that possesses two distinct NAPE-encoding genes.…”
Section: Resultsmentioning
confidence: 99%
“…Expression pattern tissue (categorical) Wormbase (29) Expression pattern lifestage (categorical) Wormbase ( 29)…”
Section: Datafield Sourcementioning
confidence: 99%